The Influence of Transformational Leadership on Company Performance with Organizational Innovation as a Mediating VariableiIn Perumda Tirta Hita Buleleng - I Gede Bobi Suryano; I Nengah Suarmanayasa; Trianasari Trianasari (Journal of Social Research, 2023)
Perumda Tirta Hita Buleleng during the 2017-2022 period has a good and healthy performance but if further analyzed the value obtained from the performance assessment decreases from year to year. This condition indicates that although performance achievements are included in the good and healthy category, there is a decrease in the quality value of governance in Perumda Tirta Hita Buleleng. This research analyzes the influence of transformational leadership on Company Performance using mediation variables in the form of organizational innovation at Perumda Tirta Hita Buleleng. The population in this study was all employees at Perumda Tirta Hita Buleleng. Determination of samples using the purposive sampling method, namely employees who have a minimum work period of 3 years and other related ones totaling 100 people. This research uses a quantitative research design, which is based on the positivism paradigm. The data in this study was collected in the form of questionnaires and the data were managed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results of this study show that: Organizational Innovation has a positive and significant effect on company performance, meaning that increasing organizational innovation in Perumda Tirta Hita Buleleng can improve company performance. Based on the research findings and analysis of the research results, it can be concluded that organizational innovation and transformational leadership have a positive and significant effect on company performance.